The Relationship between Neutrophil Lymphocyte Ratio and Hepatitis C Virus RNA in Hepatitis C Coinfected HIV Patients Receiving Direct-Acting Antiviral Therapy at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Suyata; Prabjot Singh; Harun Hudari; Taufik Indrajaya; Nurmalia Purnama Sari (HM Publisher, 2023)
Background: Hepatitis C is an inflammatory disease of the liver caused by infection with the hepatitis C virus (HCV). Inflammatory markers are significant in assessing the course of an infectious or inflammatory disease. One of them is the neutrophil-lymphocyte ratio (NLR) and the amount of HCV RNA viral load, which combines neutrophils as an active inflammatory component and lymphocytes as a regulatory and protective component in a single parameter. Research on the relationship between NLR and HCV RNA in HIV patients coinfected with HCV is still limited. This study aimed to determine the relationship between NLR and HCV RNA in HIV-HCV coinfected patients who received DAA therapy and went to the outpatient polyclinic at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: Analytic observational study. A total of 38 research subjects participated in this study. Observation of NLR was carried out using hematology analyzer, and observation of HCV RNA levels was carried out using the PCR technique. Data analysis was carried out using SPSS univariate and bivariate. Results: There was a difference between pre-post therapy NLR and pre-post therapy HCV RNA viral load, p<0.05. NLR is in line with HCV RNA viral load as a prognostic tool for successful DAA therapy in HIV patients coinfected with hepatitis C. Conclusion: There is a relationship between HIV and HCV RNA in hepatitis C coinfected HIV patients receiving direct-acting antiviral therapy at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.